‘We tried our best... it wasn’t great’: a qualitative study of clinician experiences on child psychiatry wards at the height of COVID-19 - Rachel Kronick; Isabella Kakish; Ana Gomèz-Carrillo (BMC Health Services Research)
Abstract Changing public health and hospital protocols during the height of the COVID-19 pandemic shaped the provision of inpatient mental health care. While a growing body of research explores the challenges of restrictions on adult psychiatric wards, the impact on clinical teams and epidemiological trends in youth mental health, no research has explored inpatient psychiatric hospital services for child and adolescent psychiatry during the pandemic. This study seeks to understand how clinicians in Canada working in child and adolescent mental health wards experienced caring for their patients while navigating pandemic hospital restrictions. Following a qualitative descriptive methodology and also drawing on institutional ethnography we generated data using two methods: 1) an online survey of clinicians across the country asking about experiences providing care and COVID restrictions and 2) in-depth, semi-structured interviews with clinicians. Data from 54 surveys and 14 interviews were analyzed using thematic analysis yielding two major themes. First, clinicians felt that clinical care was compromised with likely impact on patient outcomes. Second, respondents reported that the context of the pandemic provoked tensions and resistance within the clinical teams and the institution. Our findings have important implications not only for future public health crises, but also for rethinking how psychiatric care is provided and prioritized. This study points to the need for 1) mechanisms which support collaborative decision making at the institutional level, to ensure regulations are more flexible and can adapt to the needs of child mental health patients; and 2) that child psychiatry prioritize generating spaces of ethical reflection for clinical teams and institutional decision-makers so that paternalism does not trump principles of primum non-nocere (first, do no harm), autonomy and reciprocity.